Detection of previous brain infarct on PET/CT study of a Hodgkin lymphoma patient - Koç, Zehra Pinar; Unal, Kemal; Balci, Tansel Ansal; Elkiran, Emin Tamer (BMJ Publishing Group, 2011)
Positron emission tomography/CT examination was performed to 62-year-old male patient with diagnosis of Hodgkin lymphoma for treatment response which revealed complete response. During re-evaluation process of this patient in our department, asymmetrical brain metabolism defect of right thalamus and hipometabolism of right parietal lobe was observed. This finding was confirmed with additional CT imaging as a subacute infarct tissue. Copyright 2011 BMJ Publishing Group. All rights reserved.
Keywords: bleomycin; dacarbazine; doxorubicin; vinblastine; adult; article; brain infarction; brain metabolism; brain radiography; cancer chemotherapy; cancer regression; case report; clinical evaluation; clinical feature; computer assisted emission tomography; differential diagnosis; drug response; follow up; Hodgkin disease; human; male; multiple cycle treatment; neuroimaging; parietal lobe; priority journal; thalamus nucleus